Numerical Modeling and GNSS Observations of Ionospheric Depletions Due To a Small‐Lift Launch Vehicle - G. W. Bowden; M. Brown (Space Weather)
Abstract Space launches produce ionospheric disturbances which can be observed through measurements such as Global Navigation Satellite System signal delays. Here we report observations and numerical simulations of the ionospheric depletion due to a Small‐Lift Launch Vehicle. The case examined was the launch of a Rocket Lab Electron at 22:30 UTC on 22 March 2021. Despite the very small launch vehicle, ground stations in the Chatham Islands measured decreases in slant total electron content for navigation satellite signals following the launch. Global Ionosphere Thermosphere Model results indicated ionospheric depletions which were comparable with these measurements. Measurements indicated a maximum decrease of 2.7 TECU in vertical total electron content, compared with a simulated decrease of 2.6 TECU. Advection of the exhaust plume due to its initial velocity and subsequent effects of neutral winds are identified as some remaining challenges for this form of modeling.